Executive Committee Minutes 2012-01-19 - Academic Senate:::::::::
Resolution Regarding the Subsidization of Category II (Local) Student Fees for Low Income Students approved for Senate agenda. Academic Calendar 2012-2016 and Guidelines approved for Senate agenda. Faculty Eligible for Emeritus Status approved for Senate consent calendar. Statewide Senate update.